Development of decision support system for sheep and goats in the hot / dry area of the North costal zone of Egypt - Aboul Naga A.; Hassan F.; Rafea A.; Metawi H.R.; El Azhari E.S.; Osman M.A.; Fahmy F.; Rafea M. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
A Small Ruminant Decision Support System (SRDSS) was developed to improve flock productivity under the arid conditions of the North Costal Zone of Egypt. Field data were collected on 165 flocks to characterize prevailing small ruminant production systems and to identify their biological and economic potentialities and constraints. The SRDSS comprises four modules. The Flock Establishment Module displays housing, utilities, labour, flock structure and preferred breeds that best utilize the breeder resources. The Management Module displays the recommended flock practices during mating, pregnancy, parturition, lamb suckling and weaning. The Feeding Module displays recommended rations for best utilization of range, fodder and crop residues and illustrates technical means to enhance their nutritive value and best utilization of available feed resources. The Production and Marketing Module displays the biological and economic assessment of the flock production and means to improve its productivity and profitability. The SRDSS was verified and validated through local and regional workshops, and was recommended as a useful tool as a vital link between SR expertise, breeders (Bedouins) and extension staff, in remote vulnerable areas.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)